Coagulants for water based on activated aluminum alloys - R.G. Sarmurzina; G.I. Boiko; B.K. Kenzhaliyev; U.S. Karabalin; N.P. Lyubchenko; P.V. Kenyaikin; Zh.B. Ilmaliyev (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: The reduction of fresh water deficit and water-related morbidity is the most important problem of the state’s national security. The effective treatment of natural water in industrialized areas from natural and anthropogenic pollutants is the main ecological task. Coagulation is one of the effective methods used to treat water chemically to purify it. Aluminum polyoxychlorides have gained popularity because of their advantages over coagulants—aluminum and iron sulfates. No production of aluminum polyoxychloride occurs in Kazakhstan despite the need for coagulants (the minimum need is assessed at about 11 thousand tons). The work is aimed at theoretical justification and experimental proof of a principally new approach to the development of aluminum polyoxychloride production technology based on activated aluminum alloys containing metal activators, such as gallium, indium , and tin from 0.5 to 5 percent weight. In addition, the goal is solving environmental issues associated with improving the drinking water quality and related to environmental pollution with wastewater.METHODS: The microstructures, phase components, and elemental compositions of alloys and reaction products were studied by scanning electron microscopy/energy dispersive X-ray spectroscopy. The thermal effects of alloys were investigated usin thermogravimetry methods. Oil content in wastewater was determined by spectrophotometry. Oil particle dimensions and wastewater zero potentials were determined using electrophoretic light scattering method and residual turbidity by turbidimetry. Water quality assessment was included in the purified water analysis and comparison with the sanitary and epidemiological standards established for drinking water supply and wastewater intended for water discharge.FINDINGS: The structures and compositions of activated aluminum alloy containing metal activators - gallium, indium, and tin - from 0.5 to 5 weight percent and aluminum polyoxychlorides based on it were studied using modern instrumental methods. The efficiency of the treatment of natural and oil-contaminated wastewater with aluminum polyoxychloride was assessed. The treated water parameters were within the norms established for drinking water supply and wastewater disposal by Sanitary Rules and Norms 2.1.4.559-96. The efficiency of potable water treatment reached 90–99 percent.CONCLUSION: An effective and technologically simple method is developed for producing aluminum polyoxychloride. It involves dissolving an activated alloy in 1–5 percent hydrochloric acid, with an aluminum content of 98.5–85 percent. Alloy processing is carried out at temperatures ranging from 60 to 65 degree celsius. The temperature rises from 20 to 25 degree celsius to the specified optimum without heat supply from the outside due to the interaction among reagents. The process is completed in 2–3 hours. The results confirm that aluminum polyoxychloride is an effective coagulant for drinking and wastewater treatment. The treated water is within the established limits in terms of hydrogen potential, chemical oxygen demand, and turbidity. The water treatment method can be easily implemented.